The Mizo discovery of the British Raj: empire and religion in Northeast India, 1890-1920 - Jackson, Kyle (Cambridge University Press, 2023)
High in the eastern Himalayan foothills, people had a unique vantage point on the British Empire. The Mizo Discovery of the British Raj presents a history of Mizoram in Northeast India told from historical Indigenous perspectives of encounters with empire from the 1890s to the 1920s. Based on a wide range of research and enriched by sources newly digitised by the author through the British Library's Endangered Archives Programme, Kyle Jackson sheds new light on the complex and violent processes of how and why diverse populations of highland clans in the Indo-Burmese borderlands came to redeﬁne themselves as Christian Mizos. By using historical Indigenous concepts and logics to approach early twentieth-century imperial encounters, Jackson guides readers into a decolonial history of Northeast India, demonstrating the value of thinking not just about the histories of colonized peoples and concepts but also with them.